Thermoeconomic analysis of hydrogen incorporation in a biodiesel plant - Boloy, Ronney Arismel Mancebo [UNESP]; Silva, Marcio Evaristo [UNESP]; Valle, Atilio Erazo [UNESP]; Silveira, José Luz [UNESP]; Tuna, Celso Eduardo [UNESP] (Elsevier, 2017)
The paper develops a methodology that uses the thermoeconomic functional diagram applied for allocating cost of products obtained by the plant and afterwards demonstrates how it is possible to calculate the marginal cost in US$/kW h of the production. The methodology which was adopted includes the plant exergetic analysis development, the function system identification through physical diagram of the plant, construction of the Thermoeconomic Functional Diagram and the determination of the expressions for the plant's exergetic functions. The methodology also includes the determination of some parameters such as, investments, maintenance, operation, raw materials (canola oil, catalysts, methanol, glycerine and natural gas) and utility costs (electricity and steam water). As a result, it can be said that the simultaneously production of biodiesel and hydrogen is a suitable technology to minimize biodiesel production cost. About 6% of the thermoeconomic cost of biodiesel production was diminished when compared to the values previously published in the present literature. In relation to the hydrogen production thermoeconomic costs, the values are closer when they are compared to the ones which were identified in the literature. As a contribution to the scientific knowledge, it can be said that the obtained results shows the high performance of simultaneous biodiesel and hydrogen production, especially when glycerine is further processed into valuable energetic matter, in other words, considering economic aspects associated with the exergy conception, in order to develop a tool to assist the equipment operation, as well as to optimize the biodiesel plant design. Also shows that in a biodiesel production plant the hydrogen technology is more sustainable than the traditional one. The paper aims to innovate the production process of biodiesel by incorporating the hydrogen production process through glycerine steam reforming.
Keywords: Biodiesel; Cost; Functional diagram; Glycerine; Hydrogen; Thermoeconomic